Teleoperated Road Vehicles: A Novel Study on the Effect of Blur on Speed Perception. (24th September 2013) - Tang, Tito; Kurkowski, Jan; Lienkamp, Markus
The future mobility of urban areas is changing constantly; ideally, vehicles should be able to drive autonomously through traffic. Unfortunately, autonomous vehicles are not yet fully capable of matching human performance. Therefore, the teleoperation of vehicles presents a solution for this task. During teleoperation, a human driver is responsible for driving the vehicle using information transmitted from the vehicle to a working station. Unfortunately, because of the artificial environment in which the operator is located, it is very difficult to achieve high telepresence and accurate speed estimation. It is known that in order to safely drive a vehicle, it is very important to be able to correctly estimate the vehicle's speed. This paper presents a study conducted to quantify the speed perception tendency of a human operator at the working station. Additionally, it is shown that a training process can at least temporarily improve speed perception. Furthermore, the implementation of zoom blur to increase optical flow is shown to positively influence speed perception. Four hypotheses are defined and analysed to study speed perception at an operator's working station. The results are presented and discussed.